Measuring the Effects of the Uniform Settlement Rate Requirement in the International Telephone Industry - Suil Lee (KDI Journal of Economic Policy, 2020)
As a case study of an ex-post evaluation of regulations, in this paper I evaluate the `uniform settlement rate requirement', a regulation that was introduced in 1986 and that was applied to the international telephone market in the U.S. for more than 20 years. In a bilateral market between the U.S. and a foreign country, each U.S. firm and its foreign partner jointly provide international telephone service in both directions, compensating each other for terminating incoming calls to their respective countries. The per-minute compensation amount for providing the termination service, referred to as the settlement rate, is determined by a bargaining process involving the two firms. In principle, each U.S. firm could have a different settlement rate for the same foreign country. In 1986, however, the Federal Communications Commission introduced the Uniform Settlement Rate Requirement (USRR), which required all U.S. firms to pay the same settlement rate to a given foreign country. The USRR significantly affected the relative bargaining positions of the U.S. and foreign firms, thereby changing negotiated settlement rates. This paper identifies two main routes through which the settlement rates are changed by the implementation of the USRR: the Competition-Induced-Incentive Effect and the Most-Favored-Nation Effect. I then empirically evaluate the USRR by estimating a bargaining model and conducting counterfactual experiments aimed at measuring the size of the two effects of the USRR. The experiments show remarkably large impacts due to the USRR. Requiring a uniform settlement rate, for instance, results in an average 32.2 percent increase in the negotiated settlement rates and an overall 13.7 percent (3.43 billion) decrease in the total surplus in the U.S. These results provide very strong evidence against the implementation of the USRR in the 1990s and early 2000s.
Keywords: C51; C78; K23; L13; L50; L96; 330; Ex-post Evaluation; Uniform Settlement Rate Requirement; Bargaining; Competition-Induced-Incentive Effect; Most-Favored-Nations Effect